Azurin-TiO2 hybrid nanostructure field effect transistor for efficient ultraviolet detection. (23rd September 2019) - Moudgil, Akshay; Kalyani, Neeti; Mishra, Prashant; Das, Samaresh
Abstract: Hybrid semiconductor nanostructures have attracted tremendous response due to their unique properties and applications in nano-optoelectronics and sensors. Here, we fabricated a back-gated transistor based on 300 nm channel of the Azurin-TiO2 hybrid nanostructure, whose enhanced performance is attributed to the synergetic effect of the metal oxide and azurin. Surface potential mapping under the dark and light condition using Kelvin probe force microscopy, gives the perfect correlation of band gap estimation for Azurin, TiO2 and Azurin-TiO2 nanostructures. The extracted parameters of the transistor exhibit the majority carrier mobility of 2.26 cm 2 V –1 s –1, Schottky barrier height of 133.56 meV and low off current (6 × 10 −10 A). The photodetector showed the high spectral response of 8.7 × 10 5 A W −1 and detectivity of 6.4 × 10 14 Jones for 260 nm wavelength, at an applied gate bias of 5 V. The short carrier transit time (3 μ s) and large recombination time (0.4 s) with multiple recirculations of photo generated carries facilitate the high gain of 2.6 × 10 6 . A significant rejection ratio ( R 260 / R 530 ) of 56.2 at V GS = 5 V and the linear dynamic range of 45.75 dB for 260 nm wavelength is achieved. The obtained rise and fall time of the photodetector is 0.52 s, and 0.65 s, respectively. This study suggests the applicability of Azurin-TiO2 hybrid nanostructures with high performance for the biocompatible optoelectronic devices.